Caracterización por medios dependientes de cultivo de comunidades bacterianas de escarabajos estercoleros (Coleoptera: Scarabaeinae) y de suelos conservados y alterados por incendios de la Reserva El Madrigal del Podocarpus, Loja - Jiménez Barba, Josselyn Priscila (2023)
It was characterized by dependent means of communities of dung beetles (Coleoptera: Scarabaeinae) and soils conserved and altered by fires of the El Madrigal del Podocarpus Reserve were characterized by crop-dependent environments. Three study landscapes were selected (conserved, altered by fire, grassland), in each one a 10 m x 10 m plot was installed, dividing into 1 m x 1 m subplots. Three subplots were randomly selected as sampling points for the collection of soil and beetles. In each selected subplot, a modified pitfall trap baited with human feces was installed. A protocol for the dissection of the digestive tract of beetles was elaborated based on the bibliographic review. And using the striation technique, the bacterial isolation of the samples of the digestive tract and soil was carried out. In the results, 25 bacterial strains were isolated from the digestive tract of beetles, belonging to the genera: Canthidium, Uroxys, Dichotomius and Onthopagus; and 47 bacterial strains from the soil samples. According to the morphological characteristics and Gram staining, it was observed that there is a certain similarity between the bacterial communities isolated from the soil and from the digestive tract of the beetles, with a greater predominance of the presence of G + bacilli in both samples; however, from the point of view between landscapes, in the soil samples, if variation was observed, with respect to the fire landscape. These results have generated important information about the bacterial communities found in the intestines of dung beetles and in the soil of the El Madrigal Podocarpus Reserve, becoming an essential reference baseline for future researchers. Keywords: edaphic-intestinal bacterial communities, landscapes, bacterial isolation, culture-dependent media, El Madrigal del Podocarpus Reserve.